# montrer-que-x-y-z-gt-0-x-3-2y-2-4z-6xy-2-3-z-1-3-

Question Number 76904 by mpsicasa last updated on 31/Dec/19
$$\mathrm{montrer}\:\mathrm{que}: \\$$$$\forall{x},{y},{z}>\mathrm{0}\:\:{x}^{\mathrm{3}} +\mathrm{2}{y}^{\mathrm{2}} +\mathrm{4}{z}\geqslant\mathrm{6}{xy}^{\mathrm{2}/\mathrm{3}} {z}^{\mathrm{1}/\mathrm{3}} \\$$
Commented by mr W last updated on 31/Dec/19
$${A}.{M}.\geqslant{G}.{M}. \\$$$$\frac{{a}+{b}+{c}}{\mathrm{3}}\geqslant\sqrt[{\mathrm{3}}]{{abc}} \\$$$${a}+{b}+{c}\geqslant\mathrm{3}\sqrt[{\mathrm{3}}]{{abc}} \\$$$${x}^{\mathrm{3}} +\mathrm{2}{y}^{\mathrm{2}} +\mathrm{4}{z}\geqslant\mathrm{3}\sqrt[{\mathrm{3}}]{{x}^{\mathrm{3}} ×\mathrm{2}{y}^{\mathrm{2}} ×\mathrm{4}{z}}=\mathrm{6}{xy}^{\mathrm{2}/\mathrm{3}} {z}^{\mathrm{1}/\mathrm{3}} \\$$
Commented by Zainal Arifin last updated on 13/Apr/20
$$\\$$
Answered by MJS last updated on 31/Dec/19
$${f}\left({x},\:{y},\:{z}\right)={x}^{\mathrm{3}} +\mathrm{2}{y}^{\mathrm{2}} +\mathrm{4}{z}−\mathrm{6}{xy}^{\frac{\mathrm{2}}{\mathrm{3}}} {z}^{\frac{\mathrm{1}}{\mathrm{3}}} \\$$$$\mathrm{searching}\:\mathrm{for}\:\mathrm{the}\:\mathrm{minimum} \\$$$$\frac{{df}}{{dx}}=\mathrm{3}{x}^{\mathrm{2}} −\mathrm{6}{y}^{\frac{\mathrm{2}}{\mathrm{3}}} {z}^{\frac{\mathrm{1}}{\mathrm{3}}} =\mathrm{0}\:\Rightarrow\:{x}=\sqrt{\mathrm{2}}{y}^{\frac{\mathrm{1}}{\mathrm{3}}} {z}^{\frac{\mathrm{1}}{\mathrm{6}}} \\$$$$\Rightarrow \\$$$${f}\left(\sqrt{\mathrm{2}}{y}^{\frac{\mathrm{1}}{\mathrm{3}}} {z}^{\frac{\mathrm{1}}{\mathrm{6}}} ,\:{y},\:{z}\right)=\mathrm{2}{y}^{\mathrm{2}} +\mathrm{4}{z}−\mathrm{4}\sqrt{\mathrm{2}}{yz}^{\frac{\mathrm{1}}{\mathrm{2}}} \\$$$$\frac{{df}}{{dy}}=\mathrm{4}{y}−\mathrm{4}\sqrt{\mathrm{2}}{z}^{\frac{\mathrm{1}}{\mathrm{2}}} =\mathrm{0}\:\Rightarrow\:{y}=\sqrt{\mathrm{2}}{z}^{\frac{\mathrm{1}}{\mathrm{2}}} \:\Rightarrow\:{x}=\sqrt[{\mathrm{3}}]{\mathrm{4}}{z}^{\frac{\mathrm{1}}{\mathrm{3}}} \\$$$$\Rightarrow \\$$$${f}\left(\sqrt[{\mathrm{3}}]{\mathrm{4}}{z}^{\frac{\mathrm{1}}{\mathrm{3}}} ,\:\sqrt{\mathrm{2}}{z}^{\frac{\mathrm{1}}{\mathrm{2}}} ,\:{z}\right)=\mathrm{0} \\$$$$\Rightarrow \\$$$$\mathrm{0}=\mathrm{minimum}\:\mathrm{of}\:{f}\left({x},\:{y},\:{z}\right)\:\mathrm{with}\:{x},\:{y},\:{z}\:>\mathrm{0} \\$$$$\Rightarrow \\$$$${x}^{\mathrm{3}} +\mathrm{2}{y}^{\mathrm{2}} +\mathrm{4}{z}−\mathrm{6}{xy}^{\frac{\mathrm{2}}{\mathrm{3}}} {z}^{\frac{\mathrm{1}}{\mathrm{3}}} \geqslant\mathrm{0} \\$$$${x}^{\mathrm{3}} +\mathrm{2}{y}^{\mathrm{2}} +\mathrm{4}{z}\geqslant\mathrm{6}{xy}^{\frac{\mathrm{2}}{\mathrm{3}}} {z}^{\frac{\mathrm{1}}{\mathrm{3}}} \\$$